Emotional Success : The Motivational Power of Gratitude, Compassion and Pride - David DeSteno (Bluebird books for life, 2018)
A pioneering psychologist reveals the most effective route to success relies on just three emotions 'EMOTIONAL SUCCESS is as inspiring as it is practical. DeSteno shows us how to [...] improve our lives - and the world.' - Arianna Huffington, author of Thrive and The Sleep Revolution 'If you think the key to self-control is overriding your emotions, think again. Moral emotions can strengthen your willpower - and this fascinating book uses the latest social science to explain how.' - Adam Grant, author of GIVE AND TAKE, ORIGINALS, and OPTION B with Sheryl Sandberg Kick-start your motivation using gratitude, employ compassion to build your network, and take pride to maximise success. Using cutting-edge research, world-leading psychologist David DeSteno shows you how positive emotions are far more powerful than willpower and self-denial in achieving your goals. Willpower is quickly depleted, but our prosocial emotions become stronger the more we use them. Even better, they're contagious. & Cultivating gratitude, compassion, and pride leads to better cardiovascular health, immune function and sleep & Students who feel proud of their work will work 40% harder and longer than others & Empathy and compassion are the best predictors of team success Our prosocial emotions evolved specifically to help us resist immediate temptations in favour of long-term gains. But they can also be adapted to strengthen our bonds with our own future selves - who will benefit most from the grit we need to succeed in life.